A rapid and ultra-sensitive dual readout platform for Klebsiella pneumoniae detection based on RPA-CRISPR/Cas12a - Tan, Meiying; Liang, Lina; Liao, Chuan; Zhou, Zihan; Long, Shaoping; Yi, Xueli; Wang, Chunfang; Wei, Caiheng; Cai, Jinyuan; Li, Xuebin; Wei, Guijiang (Frontiers in Cellular and Infection Microbiology, 2024)
The bacterium Klebsiella pneumoniae (Kp) was the primary pathogen of hospital-acquired infection, but the current detection method could not rapidly and conveniently identify Kp. Recombinase polymerase amplification (RPA) was a fast and convenient isothermal amplification technology, and the clustered regularly interspaced short palindromic repeats (CRISPR) system could rapidly amplify the signal of RPA and improve its limit of detection (LOD). In this study, we designed three pairs of RPA primers for the rcsA gene of Kp, amplified the RPA signal through single-strand DNA reporter cleavage by CRISPR/Cas12a, and finally analyzed the cleavage signal using fluorescence detection (FD) and lateral flow test strips (LFTS).Our results indicated that the RPA-CRISPR/Cas12a platform could specifically identify Kp from eleven common clinical pathogens. The LOD of FD and LFTS were 1 fg/μL and 10 fg/μL, respectively. In clinical sample testing, the RPA-CRISPR/Cas12a platform was consistent with the culture method and qPCR method, and its sensitivity and specificity were 100% (16/16) and 100% (9/9), respectively.With the advantages of detection speed, simplicity, and accuracy, the RPA-CRISPR/Cas12a platform was expected to be a convenient tool for the early clinical detection of Kp.